Ethnobotanical and Nutritional Evaluation of Understudied Wild Edible Fruits in South Africa: Bridging Indigenous Knowledge and Food Security: A Review - Nonhlanhla Preduence Lubisi; Maropeng Erica Matlala; Luambo Jeffrey Ramarumo; Peter Tshepiso Ndhlovu (Foods)
Wild edible fruits are important for ensuring food and nutritional security, especially in developing countries like South Africa. Globally, wild edible fruits are widely distributed, and they are consumed in different parts of the world; however, they are undervalued. This systematic review consolidates existing knowledge addressing the utilization of wild edible fruits, and their nutritional benefits. A total of 74 wild edible fruit species belonging to 29 families found in South Africa were documented in this study. The nutritional composition was reported only in 41 (55.4%) fruit species. The Anacardiaceae family had the most cited species (n = 11) (14.86%), followed by the Moraceae (n = 6) (8.1%), and Cucurbitaceae and Ebenaceae, of which each had five species, each contributing 5.4% to the total documented species. Sclerocarya birrea. (A.Rich.) Hochst., Mimusops zeyheri Sond., and Strychnos spinosa Lam. are three of the most important wild fruit species contributing to food and nutritional security. This review revealed that there is a dearth of literature studies that have substantially documented the contribution of wild edible fruits in food and nutritional security. In this regard, a study on ethnobotanical evaluation incorporating wild edible fruits used by local people could significantly provide insights and enhance our understanding of indigenous and technological knowledge that could be utilized to strengthen rural food security.